THE OTTOMAN PHILIPPINES RELATIONS DURING THE AMERICAN CONTROL OF THE PHILIPPINES (1898-1916) - Ozkan, Selim Hilmi (E.U. Printing and Publishing House, 2023)
The present study attempts to investigate the resistance of Philippine people against Spanish rule in 1521 and American rule in 1898, along with their resistance against the colonialists in the Philippines, island country of Southeast Asia. Additionally, the attitude of the Ottoman Empire towards these controlled and Ottoman-Philippine relations will also be analyzed. The Philippines remained under Spanish rule for several centuries until the Americans arrived. Given that the geographical location of the Philippine islands is on one of the historically important trade route networks stretching from Europe to the Far East and the China Sea, these relations have become more crucial. During this period Captain John P. Finley, the U.S. governor of Zamboanga in the Philippines made a visit to Istanbul and tried to persuade the Ottoman administration that Muslims should not resist the American occupation by using the influence of the caliph on Muslims. The main resources of our research are based on the documents in the Presidential Ottoman Archives and their background. National and international research on the Philippines have also guided us through our research.
Keywords: Philippines; Moro Muslims; Seyid Sheikh Mehmed Vecih Efendi; Ottoman Empire; United States of America; Spain; History